Western Union Telegram from Lawrence F. O' Brien - Lawrence F. O' Brien:::::: (1968)
This Western Union telegram informs Jane Tolmach, Women's Division Chairman of the Democratic State Central Committee of California, about a Democratic National Committee regional task force program. It announces that a team of DNC specialists will conduct an area task force session on Saturday, September 21, at the Plaza Hotel in Los Angeles beginning at 3 p.m., as part of organizing efforts for the campaign. Signed by Lawrence F. O'Brien, the message urges her to attend the important meeting, which will be led by Senator Fred R. Harris of Oklahoma.